Identity of post-retirement age workers and their work experiences - Ng, Charmaine (2018)
This study examines how post-retirement age workers working in the cleaning industry in Singapore perceive their identity in the workplace as well as their work-related experiences. With the shift in demographics in the labour force due to an aging population in Singapore, older workers increasingly make up a significant part of the workforce and are viewed as a valuable asset to the economy. I therefore argue on the importance of exploring their work-based identity in relation to one’s self-esteem and performance at work through two main identity theories that contribute to the identity formation processes. Despite rising numbers of post-retirement age workers remaining and returning to work, there is little research in relation to the notion of one’s work identity. Therefore, this study seeks to fill the gap in the current literature by studying identities of these workers through their work experiences, which is crucial in state-macro policies and increasing the overall productivity in Singapore.